2016
DOI: 10.1097/md.0000000000005739
|View full text |Cite
|
Sign up to set email alerts
|

McGrath Series 5 videolaryngoscope vs Airtraq DL videolaryngoscope for double-lumen tube intubation

Abstract: Background:Many studies have shown Airtraq videolaryngoscope provided faster tracheal intubation and a higher success rate than other videolaryngoscopes. Recently, different types of videolaryngoscopes have been reported for use in double-lumen tube (DLT) intubation. However, the advantages and disadvantages between them remain undetermined for DLT intubation. In this study, we compared the Airtraq DL videolaryngoscope with the McGrath Series 5 videolaryngoscope for DLT intubation by experienced anesthesiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Not only SV but also the other videoscopes showed better success rates than Mc. The results were consistent with the previous studies on DLT intubation [ 1 , 8 , 17 , 18 , 20 , 25 , 26 , 29 , 30 , 32 , 36 , 37 ]. However, the best choices differed according to the indicators.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Not only SV but also the other videoscopes showed better success rates than Mc. The results were consistent with the previous studies on DLT intubation [ 1 , 8 , 17 , 18 , 20 , 25 , 26 , 29 , 30 , 32 , 36 , 37 ]. However, the best choices differed according to the indicators.…”
Section: Discussionsupporting
confidence: 93%
“…Four groups of devices from 14 studies were available for the analysis [ 7 , 18 , 20 , 25 , 27 30 , 32 , 33 , 35 , 37 39 ]. Eligible comparisons in the NMA are shown in Figs 3D and 4D .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was in accordance with previous studies where Airtraq VL showed better performance as compared to other non-channeled VLs. [ 14 15 16 ]…”
Section: Discussionmentioning
confidence: 99%